Controllable Synthesis and Structural Analysis of Nanohybrids with Gold Multipod Nanoparticle Cores and ZIF‐67 Shells (GMN@ ZIF‐67). Issue 12 (22nd September 2017) - Mai, Hien Duy; Le, Van Cam Thi; Pham, Thu Minh Thi; Ko, Jae‐Hyeon; Yoo, Hyojong
Abstract: Advanced hybrid nanomaterials tailored with unique morphologies and multiple functions can be synthesized by the controllable integration of two or more well‐designed components. Distinctively shaped metal cores with well‐defined coordination polymer shells can lead to synergistic structural properties in the resultant hybrid materials. Herein, we report a facile synthetic strategy for gold multipod nanoparticle (GMN) cores‐zeolitic imidazolate framework (ZIF‐67) shells (GMN@ZIF‐67) nanohybrids. Because of the structural anisotropy, which is crucial for heterogeneous seed‐induced nucleation, and uniqueness of GMNs, their combination with ZIF‐67 gives characteristic core–shell materials. The synthetic process can be readily achieved without using surfactants or capping reagents. Thus, it is potentially an environmentally friendly route to expedient nanohybrids. The material properties (i.e., surface area, size, and shape) of the resultant GMN@ZIF‐67 nanohybrids can be readily controlled by simply varying the relative amount of GMNs and ZIF‐67 precursors used. Abstract : Gold multipod nanoparticle cores–zeolitic imidazolate framework shells (GMN@ZIF‐67) nanohybrids are successfully synthesized and fully characterized. The size of the GMN@ZIF‐67 nanohybrids can be adjusted by either varying the molar ratio of ZIF‐67 precursors or the quantity of GMNs used.